Oxygen-producing hydrogel microspheres modified by nanoparticles, preparation method and application of oxygen-producing hydrogel microspheres in preparation of bone regeneration materials

The oxygen -producing gel micro -ball modified by nanometer, combined with oxygen storage and ROS removal function, solves the problem of recovery of the recycling of regeneration micro -environment in the bone defect area, realizes the continuous oxygen release and antioxidant effects, significantly promotes bone regeneration and blood vessels. generate.

CN119326947APending Publication Date: 2025-01-21THE FIRST AFFILIATED HOSPITAL OF SOOCHOW UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411459207.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The prior art is difficult to effectively restore the damaged regenerative microenvironment in the bone defect area, and oxygen therapy and local oxygen supply systems have sustainability and safety challenges in practical applications.

Method used

The oxygen -producing gel micro -ball modified by nano -grains is used to cover the SiO2 and dopamine (PDA) layer of the nanometer of the calcium nanometer and integrate it with the multi -porous GELMA microsphere to form a CAO2@SiO2@PDA (CSP) nanometer. The oxygen -producing gel micro -ball can continue to slowly release oxygen and good ROS removal capabilities.

Benefits of technology

This technology significantly enhances cell survival, stimulates the activation of osteoblasts and vascular endothelial cells, relieves oxidative stress in the bone defect microenvironment, promotes blood vessel and bone formation, breaks the vicious cycle of hypoxia-oxidative stress, and reshapes the regenerative microenvironment. environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119326947A_ABST
    Figure CN119326947A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of bone regeneration materials, and particularly relates to a nanoparticle-modified oxygen-producing hydrogel microsphere, a preparation method and application of the nanoparticle-modified oxygen-producing hydrogel microsphere in preparation of a bone regeneration material. According to the oxygen-producing hydrogel microsphere, CaO2 serves as a core and serves as an oxygen storage cavern, SiO2 and PDA are sequentially coated, CaO2 coated SiO2 coated PDA (CSP) nanoparticles are effectively integrated with a porous GelMA microsphere (GM) through amido bonds, and therefore the oxygen-producing hydrogel microsphere is endowed with the characteristic of continuously and slowly releasing oxygen and good ROS removing capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of bone regeneration materials, and specifically relates to a nanoparticle-modified oxygen-producing hydrogel microsphere, a preparation method and application of the microsphere in preparing bone regeneration materials. Background Art

[0002] Bone defect and poor healing are one of the most common serious complications of fractures, which not only imposes a huge burden on the socioeconomic situation, but also greatly affects the quality of life of patients. Unfortunately, achieving optimal repair of fractures and large bone defects remains a huge challenge. Regeneration of damaged bone tissue is a complex dynamic process involving complex interactions between cells and their microenvironment. After fracture, damaged blood vessels hinder the delivery of oxygen to the bone defect area, forming a hypoxic microenvironment around the affected area. The unfavorable hypoxic microenvironment not only inhibits the proliferation and differentiation of mesenchymal stem cells / stromal cells (MSCs), but also impairs the aerobic metabolism and function of repair cells involved in bone regeneration. The expression of osteogenic-specific genes is significantly downregulated, and the synthesis and mineralization process of collagen I are also negatively affected. In recent decades, various new biomaterials with specific biological functions have been designed in the field of bone tissue engineering, providing new approaches for the treatment of bone defects. However, their therapeutic effects are still limited because they fail to effectively restore the damaged regenerative microenvironment in the bone defect area. Ideal biomaterials need to not only promote the integration of materials and cells, but also promote endogenous repair and regeneration of damaged bone tissue by regulating the disordered microenvironment.

[0003] Previous studies have demonstrated the effectiveness of oxygen therapy in promoting fracture healing, and hyperbaric oxygen therapy has been recommended as an adjunctive treatment for traumatic bone ischemia and nonunion. However, as a systemic oxygen delivery strategy, it cannot continuously provide sufficient oxygen to the hypoxic area and has the potential risk of oxygen toxicity. To address the problem of hypoxia in the tissue microenvironment, various local oxygen supply systems have been designed, including perfluorocarbons (PFCs), catalase-like nanozymes, and solid inorganic peroxides. However, these systems still face unresolved challenges in practical applications. Specifically, as oxygen carriers, PFCs significantly reduce the sustainability of oxygen supply in oxygen-deficient environments. In addition, the lack of oxygen supply can be improved by utilizing catalase-like nanomaterials to convert endogenous hydrogen peroxide at the injury site into oxygen. Their poor oxygen production capacity makes them ineffective in alleviating long-term hypoxia during the osteogenesis stage. Currently, calcium peroxide (CPO) has attracted considerable attention in the field of tissue engineering due to its significant oxygen generation performance. The main reason associated with the application of CPOs is the limited controllability of their oxygen release, resulting in unpredictable oxygen release kinetics and potential excessive accumulation of hydrogen peroxide, both of which are detrimental to bone repair. Encapsulation of CPOs with a hydrophobic barrier has been shown to be a viable approach to enhance stability and optimize oxygen release, thereby improving their biosafety. Additionally, an independent study demonstrated that the silica shell barrier can significantly attenuate the diffusion of gas molecules released from the inner nanoparticles, effectively prolonging their release and enabling precise control of the reaction process. Similarly, encapsulation of CPOs within a silica shell ensures stable and continuous oxygen generation while minimizing potential cytotoxic effects, which is in line with the oxygen supply requirements for bone defect tissue regeneration. In addition, it has been recognized that Ca 2+ and silicates can promote osteogenesis, and the clever integration of these bioactive elements into oxygen-supplying biomaterials can promote bone regeneration.

[0004] Accumulating evidence indicates that hypoxia leads to excessive production of reactive oxygen species (ROS), disrupting ROS homeostasis and inducing oxidative stress. Oxidative damage can lead to mitochondrial dysfunction, DNA and protein damage, and ultimately cause apoptosis of a large number of osteoblasts and inhibition of osteogenic differentiation of bone marrow mesenchymal stem cells (BMSCs). In turn, excessive ROS not only hinder angiogenesis but also consume local oxygen, which may aggravate hypoxia and form a vicious cycle. In previous studies, catalase (CAT) was incorporated into oxygen-releasing hydrogels to endow them with ROS scavenging ability, enabling the hydrogels to reverse oxidative stress while alleviating hypoxia. Unfortunately, the poor stability and reduced antioxidant efficiency of natural enzymes under adverse conditions (e.g., redox imbalance or acidic environment) have been overlooked. Dopamine (PDA) is a natural biopolymer that has shown remarkable ROS scavenging effects, with a broad spectrum of free radical neutralization ability and high stability under physiological conditions. In addition, PDA has become a promising candidate for nanoparticle surface functionalization due to its excellent biocompatibility, biodegradability, extraordinary adhesion properties, and mild synthesis requirements. At the same time, the integration of PDA coating with superoxide dismutase and catalase mimic activity can also effectively decompose the excess hydrogen peroxide produced in the CaO2 reaction. However, there are few studies on the application of PDA in bone regeneration materials, so there is an urgent need to provide a biocompatible nanocomposite material with good antioxidant and oxygen supply properties. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a nanoparticle-modified oxygen-producing hydrogel microsphere, a preparation method and its application in the preparation of bone regeneration materials, with CaO2 as the core as the "oxygen reservoir", and SiO2 and PDA are coated in sequence, and the CaO2@SiO2@PDA (CSP) nanoparticles are effectively integrated with porous GelMA microspheres (GM) through amide bonds, thereby giving the oxygen-producing hydrogel microspheres the characteristics of continuous and slow oxygen release and good ROS scavenging ability.

[0006] The technical solution provided by the present invention is as follows:

[0007] A preparation method of nanoparticle-modified oxygen-producing hydrogel microspheres comprises the following steps: dissolving calcium peroxide nanoparticles in anhydrous ethanol solution, ultrasonically treating the solution to make it uniformly suspended, then adding ammonia water, stirring and dropwise adding ethanol and tetraethyl orthosilicate, continuously stirring and then centrifuging to obtain nano-CaO2@SiO2; mixing the nano-CaO2@SiO2 with dopamine hydrochloride to react, to obtain nano-CaO2@SiO2@PDA; uniformly dispersing the nano-CaO2@SiO2@PDA in deionized water, adding activated porous GelMA hydrogel microspheres, stirring and obtaining nano-particle-modified oxygen-producing hydrogel microspheres.

[0008] Furthermore, the activation method of the porous GelMA hydrogel microspheres includes: adding the porous GelMA hydrogel microspheres, 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride, and N-hydroxysuccinimide to MES buffer in sequence, incubating and centrifuging to obtain activated microspheres; uniformly dispersing nano-CaO2@SiO2@PDA in deionized water, adding the activated microspheres, and stirring to obtain nanoparticle-modified oxygen-producing hydrogel microspheres.

[0009] Furthermore, the incubation condition is 35-40° C. for 10-20 minutes.

[0010] Furthermore, the preparation method of the porous GelMA hydrogel microspheres includes: using GelMA solution as the inner dispersed phase and isopropyl myristate solution as the outer dispersed phase, using a microfluidic device to synchronously polymerize the microspheres under ultraviolet irradiation, collecting the obtained GelMA microspheres, and purifying them using 75% ethanol and PBS, and then freeze-drying to obtain porous GelMA hydrogel microspheres.

[0011] Furthermore, the preparation method of the GelMA solution includes: adding methacrylic anhydride dropwise to a gelatin solution under light-proof conditions, stirring the solution to allow it to react fully, adding preheated PBS to terminate the reaction, and continuing to stir; dialyzing the solution to obtain a GelMA solution.

[0012] Furthermore, the preparation method of the gelatin solution includes: dissolving gelatin in PBS, and stirring at 50-70° C. for 50-70 minutes to obtain the gelatin solution.

[0013] Furthermore, the preparation method of the calcium peroxide nanoparticles comprises: dissolving anhydrous calcium chloride in double distilled water. Then, adding ammonia water and polyethylene glycol to the solution under magnetic stirring; gradually adding hydrogen peroxide solution to the mixture through a micropump; after continuous stirring, gradually introducing sodium hydroxide solution and continuously stirring to obtain a suspension; centrifuging the suspension, washing the product and vacuum drying to obtain calcium peroxide nanoparticles.

[0014] The present invention also provides nanoparticle-modified oxygen-producing hydrogel microspheres, which are prepared by the above-mentioned preparation method.

[0015] The present invention also provides the use of the above-mentioned nanoparticle-modified oxygen-producing hydrogel microspheres in the preparation of bone regeneration materials.

[0016] Furthermore, the bone regeneration material is used to promote cell survival, stimulate activation of osteoblasts and vascular endothelial cells and / or alleviate oxidative stress in the bone defect microenvironment.

[0017] Furthermore, the bone regeneration material is used to maintain cell viability under hypoxic conditions and promote angiogenesis and bone formation.

[0018] Furthermore, the bone regeneration material is used to reduce the ROS level in bone cells and mitochondria, and to increase the levels of mitochondrial membrane potential (MMP) and ALP.

[0019] Furthermore, the bone regeneration material is used to improve the mitochondrial function of bone cells under hypoxic conditions.

[0020] Furthermore, the bone regeneration material is used to promote the lumen formation process of vascular endothelial cells.

[0021] Furthermore, the bone regeneration material is used to increase the calcium deposition level of bone cells.

[0022] Furthermore, the bone regeneration material is used to increase the expression levels of Runx2, early osteogenesis-related gene Alp, and late osteogenesis-related gene Ocn in cells.

[0023] Beneficial Effects

[0024] Gelatin methacrylic anhydride (GelMA) is a widely used biomaterial known for its excellent biocompatibility, which can be made into hydrogel microspheres of uniform size by microfluidic technology. In addition, the amino groups in the PDA coating promote the effective grafting of nanoparticles onto GelMA microspheres. As a superior carrier of nanoparticles, micro-nano hydrogel microspheres can provide optimal physical support and living microenvironment for repair cells and effectively improve the unfavorable microenvironment by local delivery of nutrient factors. Therefore, this multifunctional platform can synergistically integrate the respective advantages of nanozymes and hydrogels to optimize the regenerative repair effect.

[0025] The present invention develops an oxygen supply structure that integrates ROS scavenging ability by utilizing an engineered "multifunctional integrated" hydrogel microsphere system. Specifically, the composite nanoparticles are based on CaO2 as the core, which serves as an "oxygen reservoir" and is coated with SiO2 and PDA in sequence to construct a layered structure with a core-shell. This design ensures that the oxygen in the core is fully released, while the SiO2@PDA shell makes the hydrolysis reaction of CaO2 controllable, effectively converting harmful intermediates and excess ROS into O2. Subsequently, the CaO2@SiO2@PDA (CSP) nanoparticles are effectively integrated with porous GelMA microspheres (GM) through amide bonds, thereby endowing the characteristics of sustained slow oxygen release and good ROS scavenging ability. This approach can enhance the effectiveness of functionalized microspheres (CSP-GM) in promoting cell survival, stimulating osteoblast and vascular endothelial cell activation, and alleviating oxidative stress in the bone defect microenvironment. In addition, the present invention also explores the potential mechanism of anti-oxidative stress. Finally, the bone regeneration ability of nanocomposite microspheres was demonstrated using a rat femoral condyle bone defect model. Benefiting from its stable oxygen release and powerful ROS scavenging ability, the multifunctional microsphere system showed promising potential in enhancing cell survival, restoring mitochondrial function, and alleviating oxidative stress under hypoxic conditions. More importantly, this system demonstrated the ability to enhance angiogenesis and osteogenesis, indicating that the combined effects of oxygen supply and ROS scavenging can break the vicious cycle of hypoxia-oxidative stress and reshape the regenerative microenvironment, thereby playing a synergistic therapeutic role in treating bone defects. In conclusion, our findings suggest that this novel micro oxygen reservoir system, integrating oxygen supply nanomaterials into biocompatible hydrogel microspheres, provides a promising strategy for bone tissue regeneration. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 Schematic diagram of the preparation of composite oxygen-producing microspheres and their promotion of vascularized bone regeneration through multi-faceted bone microenvironment regulation. A) Schematic diagram of the preparation of composite CaO2@SiO2@PDA (CSP) oxygen-producing nanomaterials with reactive oxygen species (ROS) scavenging enzyme activity. B) Functionalized GelMA hydrogel microspheres (CSP-GM) were prepared by covalently grafting CSP-NPS. CSP-GM hydrogel microspheres promoted the repair of critical femoral condyle bone defects in rats through dual activation of angiogenesis-osteogenesis and local microenvironment regulation.

[0027] Figure 2Synthesis and characterization of composite oxygenated nanoparticles. A) Synthesis structure diagram of CSP. Representative transmission electron microscopy (TEM) images of B) CaO2, C) CaO2@SiO2 (CS), and D) CSP. E) Corresponding energy dispersive X-ray spectroscopy (EDS) elemental mapping of CSP. F) Particle size distribution and G) Zeta potential of CaO2, CS, and CSP. H) X-ray diffraction (XRD) patterns of CaO2, SiO2, SiO2@PDA (SP), CS, and CSP. I) X-ray photoelectron spectroscopy (XPS) spectra of CSP, J) O1S of CSP, and K) C 1S. L) ABTS, M) O2 of CSP-NPS with different concentrations. •- , and N) H2O2 removal efficiency.

[0028] Figure 3 XPS high-resolution spectra of CSP. A) Ca 2p, B) Si 2p and C) N 1s.

[0029] Figure 4 Preparation and characterization of composite microspheres. A) Schematic diagram of the process of grafting nanoparticles (NPs) onto GelMA microspheres. B) Optical microscopic morphology of GelMA microspheres. C) Particle size distribution of GelMA microspheres. D) Scanning electron microscopy (SEM) images of different microspheres and their enlarged surface morphology. E) Elemental mapping image of CSP-GM. F) Surface roughness of different microspheres scanned by atomic force microscopy (AFM). G) Oxygen release curves of different nanoparticles and H) microspheres in PBS at different times.

[0030] Figure 5 Scanning electron microscopy (SEM) mapping analysis of GelMA microspheres.

[0031] Figure 6 The biocompatibility and cytoprotective effects of the composite microspheres in a hypoxic microenvironment. A) Schematic diagram of the effect of microspheres on the proliferation and adhesion of BMSCs in a hypoxic microenvironment. B) Proliferation of BMSCs at 1, 3, and 5 days was detected by CCK-8. C) Live / dead (scale bar, 100 μm) and D) cytoskeleton (F-actin, scale bar, 100 μm) fluorescence staining of BMSCs cultured on microspheres for 3 and 5 days.

[0032] Figure 7Intracellular reactive oxygen species (ROS) scavenging and antioxidant properties of composite microspheres in hypoxic microenvironment. A) Fluorescence staining of intracellular ROS in BMSCs detected by DCFH-DA probe (scale bar, 200 μm). B) Quantitative analysis of DCFH-DA fluorescence intensity in BMSCs. C) Fluorescence staining of mitochondrial ROS (MitoTracker / MitoSOX) (scale bar, 10 μm). D) Quantitative analysis of MitoSOX fluorescence intensity. E) Fluorescence labeling detection (scale bar, 20 μm) and F) Quantitative analysis of JC-1 mitochondrial membrane potential in BMSCs. G) Relative mRNA expression of antioxidant-related genes (Nr2l2, Hmox-1, Sod2) in BMSCs at 24 h detected by qRT-PCR.

[0033] Figure 8 Figure 2 shows the angiogenic activity of composite microspheres in a hypoxic microenvironment. A) Gene set enrichment analysis (GSEA) of the Hif-1 signaling pathway in BMSCs. B) GSEA analysis of the VEGF signaling pathway. C) Relative expression of Hif-1α mRNA in BMSCs at 24 hours detected by qRT-PCR. D) Relative expression of Vegf mRNA. E) Schematic diagram of the effect of microspheres on angiogenesis of HUVECs in a hypoxic microenvironment. F) Assessment of HUVECs migration by wound healing assay (scale bar, 500 μm). G) Matrigel tube formation assay of HUVECs (scale bar, 500 μm). H) Quantitative analysis of the scratch assay. Quantitative analysis of tube formation assay, including I) number of nodes, and J) total length.

[0034] Fig. 9 The activity of composite microspheres in promoting osteogenesis in a hypoxic microenvironment is studied. A) Alkaline phosphatase (ALP) staining images of a single microsphere after 7 days of osteogenic induction (scale bar, 100 μm). B) Quantitative analysis of ALP activity. C) ARS staining images of a single microsphere after 14 days of osteogenic induction (scale bar, 100 μm). D) Quantitative analysis of calcium nodule content. E) Quantitative analysis of immunofluorescence staining intensity of Runx2 and F) OCN. G) Microscopic image of immunofluorescence staining of Runx2 of a single microsphere (scale bar, 100 μm). H) Microscopic image of immunofluorescence staining of OCN of a single microsphere (scale bar, 100 μm). qRT-PCR was used to detect the relative expression levels of I) Alp, J) Runx2 at 7 days of osteogenic induction and K) Ocn mRNA at 14 days of osteogenic induction.

[0035] Fig.10Figure 2 shows the bone regeneration effect of composite microspheres in a critical femoral condyle bone defect model in rats. A) Schematic diagram of composite microspheres implanted into critical femoral condyle bone defects in rats. B) Immunofluorescence staining of Hif-1α and Nrf2 in the defect area 2 weeks after surgery (scale bar, 200 μm). C) 2D and 3D reconstructed images of femoral condyle bone defects 2 and 4 weeks after implantation (scale bar, 1.5 mm). DG) Quantitative analysis of bone volume / total volume (BV / TV), bone mineral density (BMD), trabecular separation (Tb.Sp), and trabecular thickness (Tb.Th) obtained by microCT scanning.

[0036] Fig.11 Histological staining of bone regeneration in rat femoral condyle defect. A) H&E staining and Masson staining under light microscopy at 2 weeks after surgery. B) H&E staining and Masson staining under light microscopy at 4 weeks after surgery. (The scale bars of the images are 2 mm and 500 μm, respectively).

[0037] Fig.12 Immunofluorescence staining of angiogenesis and osteogenesis in rat femoral condyle bone defect. A) CD31, B) Runx2, C) OCN immunofluorescence staining of bone defect area 4 weeks after surgery (the scale bars for the left and right magnified images are 500 μm and 200 μm, respectively). D) Quantitative analysis of CD31, E) Runx2, F) OCN positive areas. DETAILED DESCRIPTION

[0038] Example 1

[0039] A preparation method, such as Figure 1 As shown, the following steps are included:

[0040] 1. Preparation of composite nanoparticles CaO2@SiO2@PDA (CSP-NPs) and nano-microsphere composites CSP-GM:

[0041] (1) Synthesis process of calcium peroxide nanoparticles (CaO2)

[0042] Calcium peroxide nanoparticles were synthesized by hydrolysis precipitation method. The specific steps include: first, anhydrous calcium chloride (CaCl2·2H2O, 300 mg) was dissolved in 3 mL of double distilled water. Then, 2 mL of ammonia water (NH3.H2O, 1M) and 12 mL of polyethylene glycol (PEG-200) were added to the solution under magnetic stirring. Then, 1.5 mL of hydrogen peroxide (H2O2, 30% w / w) solution was gradually added to the stirred mixture at a rate of 0.04 mL / min through a micropump. The mixture was stirred for 2 hours to obtain a yellow solution. Subsequently, sodium hydroxide solution (NaOH, 0.1M) was gradually introduced with continuous stirring to adjust the pH to 11.5 to form a white suspension. Then, the suspension was centrifuged at 12,000 rpm for 15 minutes to separate the calcium peroxide nanoparticles. The obtained calcium peroxide nanoparticles were sequentially washed with NaOH solution and anhydrous ethanol, and finally vacuum dried.

[0043] (2) Nano-CaO2@SiO2 Synthesis Process

[0044] 2 mg of calcium peroxide nanoparticles were dissolved in 25 mL of anhydrous ethanol solution and then sonicated for 10 minutes to ensure uniform suspension. Subsequently, 1 mL of ammonia water (28 wt.%) was added and stirred at room temperature for 1 hour. Then, 9.8 mL of ethanol and 0.2 mL of tetraethyl orthosilicate (TEOS) were added dropwise over 3 hours using a micropump and stirred continuously for 12 hours. The mixture was centrifuged at 12,000 rpm for 10 minutes to collect the product, which was then washed 3 times with ethanol to remove unreacted precursors. The resulting product, nano-CaO2@SiO2, was stored after drying.

[0045] (3) Synthesis process of nano-CaO2@SiO2@PDA

[0046] 50 mg of nano-CaO2@SiO2 was added to 25 mL of Tris-HCl buffer solution (10 mM, pH 8.5) and then ultrasonically dispersed for 5 minutes. Subsequently, 25 mg of dopamine hydrochloride (PDA) was added and the mixture was stirred for 6 hours to promote PDA coating. After that, the composite nanomaterials coated with PDA coating were collected by centrifugation and washed 3 times with deionized water to remove unreacted impurities to obtain nano-CaO2@SiO2@PDA. Finally, nano-CaO2@SiO2@PDA (CSP) was stored at 4 °C for future use.

[0047] 2. Preparation of Gelatin Methacryloyl (GelMA) Hydrogel Microspheres

[0048] First, gelatin (20 g) was dissolved in 200 mL of PBS and stirred at 60 °C for 1 hour to ensure complete dissolution to obtain a 10% (w / v) uniform gelatin solution. Then, 16 mL of methacrylic anhydride (MA) was added dropwise at a rate of 0.25 mL per minute using an infusion pump under light-protected conditions. The mixture was stirred continuously at 60 °C for 2 hours. Afterwards, 800 mL of preheated PBS (40-60 °C) was added to terminate the reaction, and stirring was continued for 15 minutes. The solution was then dialyzed using a dialysis bag (12-14 kDa) for 2 weeks. Finally, the purified GelMA solution was lyophilized and stored at -20 °C for future use.

[0049] GelMA hydrogel microspheres were prepared by oil-in-water microfluidics. First, a coaxial electrospinning needle (needle outer diameter 30G, inner diameter 21G) was connected to a micropump using a silicone tube to form a microfluidic device. The inner dispersed phase consisted of a 7% (w / v) GelMA solution containing 0.5% (w / v) photoinitiator, and the outer phase was an isopropyl myristate solution containing 10% (w / w) Span 80. GelMA droplets were generated in the inner aqueous phase by coaxial shearing of the continuous oil phase. A continuous uniform, monodisperse spherical droplet flow was successfully generated by precisely adjusting the flow rate parameters of the two phases. Then, the microspheres were simultaneously polymerized under ultraviolet (UV) irradiation. Finally, the uniform GelMA microspheres were collected and purified using 75% ethanol and PBS, followed by freeze-drying to obtain porous GelMA hydrogel freeze-dried microspheres.

[0050] 3. Preparation of Nanoparticle-modified Oxygen-producing Hydrogel Microspheres

[0051] A certain amount of porous GelMA hydrogel freeze-dried microspheres, 16 mg of 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride (EDC) and 24 mg of N-hydroxysuccinimide (NHS) were weighed and added to 5 mL of MES buffer (pH 6.0) in sequence, so that the GelMA hydrogel microspheres were completely immersed in the solution. After incubation at 37 ° C for 15 minutes, the activated microspheres were collected by centrifugation. Subsequently, nano-CaO2@SiO2@PDA was uniformly dispersed in 10 mL of deionized water, and then the activated microspheres were added. The mixture was stirred at 37 ° C overnight to obtain nanoparticle-modified oxygen-generating hydrogel microspheres (nano-microsphere complex CSP-GM).

[0052] Example 2

[0053] 1. Characterization of composite nanoparticles CSP-NPs and nano-microsphere composites CSP-GM

[0054] Dynamic light scattering (DLS, Malvern Zetasizer Nano ZS-90, UK) was used to measure the particle size and Zeta potential of the nanomaterials. Transmission electron microscopy (TEM, Hitachi HT7700, Japan) was used to observe the morphology of the nanoparticles. X-ray photoelectron spectroscopy (XPS, Thermo Fisher Scientific, USA) was used to analyze the elemental composition of the nanomaterials, and X-ray diffraction (XRD, Bruker D8, Germany) was used to analyze the phase of the nanomaterials. Fourier transform infrared spectroscopy (FTIR) instrument (Thermo Scientific, Nicolet 6700, USA) was used to detect the chemical structure of the nanomaterials. The morphology and surface elemental composition of different microspheres were detected by scanning electron microscopy (SEM, Hitachi S 4800, Japan), and X-ray spectroscopy (EDS) was used to map the distribution of test elements to confirm the successful combination of microspheres and nanoparticles. The surface roughness of the nano-microsphere composite was examined using atomic force microscopy (AFM, Bruker, Dimension FastScan, Germany).

[0055] according to Figure 2 Following the synthesis process described in A, CSP-NPS were synthesized and characterized using transmission electron microscopy (TEM) and energy dispersive X-ray spectroscopy (EDS) elemental mapping. TEM images confirmed the unique core-shell structure of CSP-NPS, showing the gradual encapsulation of the CaO2 core by SiO2 and PDA layers ( Figure 2 BD). EDS mapping shows the spatial distribution of calcium (Ca), oxygen (O), silicon (Si) and nitrogen (N) in the nanoparticles, further confirming the successful synthesis of CSP-NPS ( Figure 2 E). Dynamic light scattering (DLS) depicts the gradual increase in particle size distribution from initial CaO2 (64.33 ± 1.39 nm) to complete SiO2 layer coating (112.80 ± 2.13 nm) and final CSP-NPS (150.27 ± 2.12 nm), which is consistent with the TEM results ( Figure 2 F). Moreover, the change of Zeta potential also reflects the coating process of SiO2 and PDA layer during the whole synthesis stage. Figure 2 As shown in G, the zeta potential of CaO2 nanoparticles was measured to be 4.81±0.45 mV, which became -14.70±0.40 mV after being coated with SiO2, and further became -25.17±0.42 mV after being coated with PDA. This is proved by the change of zeta potential ( Figure 2 G).

[0056] In order to confirm the elemental composition of CSP-NPS, X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS) were performed on the materials. Figure 2 H) exhibits characteristic diffraction peaks at 29.8°, 36.2°, 48.0° and 61.5°, which are consistent with the (002), (110), (112) and (202) crystal planes of CaO2 (JCPDS PDF card NO. 03-0865). In contrast, the SiO2@PDA (SP) layer shows an amorphous crystal structure. The SP layer deposited on the surface of the core CaO2 did not change its peaks or introduce additional diffraction peaks, thus confirming that the amorphous SP was successfully loaded onto CaO2 while maintaining the integrity of the CaO2 crystal structure. XPS spectrum ( Figure 2 I) The composition and chemical state of the nanoparticles were elucidated, and the presence of Ca, O, Si, C, and N was confirmed, which was consistent with the EDS element mapping results. The Ca 2p spectrum showed two peaks at 347.4 eV and 350.9 eV, corresponding to Ca 2p3 / 2 and Ca 2p1 / 2, respectively, indicating that calcium is in the form of divalent Ca 2+ ) ion Ca 2+ exists in the form of Figure 3 A). In the high-resolution spectrum of O 1s, OO was observed at 532.4 eV, indicating the presence of a peroxide group ( Figure 2 J). The 2p spectrum of Si at 103.3 eV corresponds to the Si-O bond in the SiO2 layer ( Figure 3 B). Figure 2 As shown in Figure 1, the peaks at 284.8, 286.2, and 288.6 eV in the C 1s spectrum correspond to CC, CO / CN, and C=O groups in the PDA coating, respectively. The C=O peak at 288.6 eV can be attributed to the oxidation of catechol during the self-polymerization of PDA. The peaks at 398.7 and 400.0 eV in the N 1s spectrum are attributed to CN and -NH2 in the PDA layer, respectively. Figure 3 C). These findings confirm the successful synthesis of CaO2 and its sequential coating with SiO2 and PDA.

[0057] In the present invention, we prepared GelMA microspheres with controllable particle size and rich porous structure through microfluidics and freeze-drying technology. As an ideal carrier, GelMA microspheres provide a good basis for the grafting of nanoparticles, effectively enhance the efficacy of nanoparticles, and achieve their sustained release ability. In the 1-ethyl-3-[3-dimethylaminopropyl]carbodiimide hydrochloride (EDC) / N-hydroxysuccinimide (NHS) coupling system, the amino groups in the outer layer of PDA cross-linked with the carboxyl groups of GelMA microspheres, promoting the successful grafting of CSP nanoparticles, and preparing multifunctional micro-nanospheres (CSP-GM, Figure 4 A). Optical microscopy images confirmed the uniform dispersion and consistent morphology of the hydrogel microspheres, with an average particle size of 406.26 ± 11.28 μm ( Figure 3 B, 3C). We further used scanning electron microscopy (SEM) and EDS to analyze the freeze-dried GelMA microspheres. Figure 4 As shown in Figure D, each group of microspheres exhibited a regular morphology and microporous structure, indicating that they have the potential to provide a favorable microenvironment for promoting cell growth and proliferation. The local magnified image of the microspheres shows the roughness of the microsphere surface and the uniform attachment distribution of the nanoparticles, indicating the effective loading of the nanoparticles on the microsphere surface after grafting. EDS analysis clearly shows that in contrast to the presence of only C, N and O elements in the unmodified GelMA microspheres, the corresponding elements C, N, O, Ca and Si are evenly distributed in the CSP-GelMA microspheres. Figure 4 E, Figure 5 ). Subsequently, atomic force microscopy (AFM) was used to evaluate the surface roughness and nanoscale topology of the composite microspheres. Consistent with the SEM findings, AFM observations provided similar information about the surface structure, with an increase in roughness caused by the incorporation of nanoparticles observed in the composite microspheres ( Figure 4 F). Therefore, these experimental results demonstrate that CSP-NPS were successfully grafted onto GelMA microspheres.

[0058] 2. Determination of free radical scavenging performance of composite nanoparticles CSP-NPs

[0059] ABTS radical scavenging assay: The total antioxidant capacity of CSP-NPs was investigated using 2,2'-azino-bis-3-ethylbenzothiazoline-6-sulfonic acid (ABTS) radical scavenging assay. ABTS was converted into its free radical form ABTS+• by reacting with potassium persulfate solution. Different concentrations of CSP-NPs (20, 40, 60, 80, and 100 μg mL -1 ) was introduced into the ABTS+• solution and incubated for 10 minutes. Finally, the absorbance of the resulting solution was measured at 734 nm. The results are shown in Figure 2 As shown in Figure 5, the concentration-dependent decrease in absorbance at 734 nm indicated the powerful free radical scavenging ability of CSP-NPs.

[0060] O2 •- Free radical scavenging assay: The pyrodealcoholation autooxidation method was then used to evaluate the superoxide anion (O2 •- ) scavenging effect. In this process, pyrodeolation was reacted with NPs at different concentrations ranging from 0 to 80 μg mL^-1 for 30 min in the dark. After the reaction period, the mixture was centrifuged and the absorbance of the supernatant was measured at 320 nm. The results are shown in Figure 2As shown in Figure 2, the absorption peak at 320 nm decreased significantly, which indicates that they are effective in scavenging O2 •- Consistent with the ABTS experimental results, O2 •- The scavenging activity was concentration-dependent ( Figure 2 M).

[0061] H2O2 scavenging assay: The hydrogen peroxide (H2O2) scavenging efficiency of CSP-NPs was evaluated by measuring the inhibition of indigo carmine oxidation. Solutions containing H2O2 (5 mM) and indigo carmine (75 μM) were prepared and incubated with different concentrations of NPs in the dark for 24 h. After incubation, the mixture was centrifuged and the absorbance of the supernatant was measured at 610 nm. The results are shown in Figure 2. Figure 2 N shows that in the absence of CSP NPs, the absorption peak at 610 nm decreases sharply due to the decomposition of indigo carmine dye in the presence of H2O2. After the addition of CSP-NPs, the absorbance at 610 nm is retained, highlighting its remarkable H2O2 scavenging efficiency.

[0062] 3. Oxygen release kinetics of composite nanoparticles CSP-NPs and nano-microsphere composites CSP-GM

[0063] To evaluate the oxygen production capacity of biomaterials, the prepared nanoparticles and microspheres were immersed in phosphate buffered saline (PBS, pH 7.4) and incubated at 37 °C. Blank PBS without any test materials was set as the control group. At different preset time points, the dissolved oxygen concentration was measured using a dissolved oxygen meter (Smart Sensor, China). The results are shown in Figure 2. Figure 4 As shown in Figure G, the O2 release of CaO2 nanoparticles initially increased rapidly, reaching a peak of 23.3 mg / L within the first 12 hours, and then decreased significantly under physiological conditions (pH 7.4, 37 °C) and returned to baseline levels after 3 days. After coating its surface with a hydrophobic SiO2 shell, the stability and duration of O2 release from CaO2 were significantly enhanced and extended to nearly 1 week, indicating that the SiO2 shell can effectively regulate and prolong the behavior and time of O2 release from CaO2. When CSP-NPs were combined with GelMA microspheres, a significantly prolonged and sustained O2 release of more than 20 days was observed ( Figure 4 H). This extended release property is beneficial for maintaining cell viability under hypoxic conditions and promoting angiogenesis and osteogenesis, thus providing a favorable microenvironment for the treatment of bone damage.

[0064] Example 3

[0065] In vitro testing of multifunctional oxygen-generating nano-microsphere complexes

[0066] 1. Cell viability and proliferation assay

[0067] In the Anaeropack anaerobic system, bone marrow mesenchymal stem cells (BMSCs) were co-incubated with microspheres under hypoxic conditions, and cell proliferation and material biocompatibility were evaluated by live / dead staining and cell counting kit-8 (CCK-8) assay. CSP-GM was washed five times in sterile PBS and then plated on the bottom of a 24-well plate. About 100 microspheres were placed in each well, and then BMSCs were seeded. The culture was terminated on the third and fifth days of co-culture, and the culture medium was removed and cell live and dead staining solution was added. After incubation at 37 °C for 30 minutes, the cell morphology and live / dead cell distribution on the microspheres were observed using a fluorescence microscope (Carl Zeiss, Germany). In addition, the proliferation activity of cells on the microspheres was evaluated by CCK-8 assay. BMSCs (2×10 4 ) were placed in a Transwell co-culture system with microspheres for co-culture. At 1 day, 3 days, and 5 days, culture medium containing 10% CCK-8 reagent (Dojindo Japan) was added. After incubation at 37 °C for 4 hours, 100 μL of the supernatant was transferred to a 96-well plate, and the absorbance (OD) at 450 nm was measured using a microplate reader (BioTek USA). The results are shown in Figure 6 As shown in the figure, under the hypoxic microenvironment, BMSCs co-cultured with microspheres showed similar proliferation activity in all groups on day 1. After 5 days of co-culture, the cell proliferation rate of the group treated with composite microspheres was significantly higher than that of the GM group. Among them, the cell proliferation increased most significantly in the CSP-GM group, followed by the CS-GM and SP-GM groups ( Figure 6 B). Live / dead staining experiments showed that as the incubation time was extended to 3 and 5 days, the number of live cells on the surface of CSM-GM increased significantly, while the live cell density in the GM group had only minimal changes ( Figure 6 C).

[0068] 2. Cytoskeleton staining

[0069] Phalloidin / DAPI staining was used to evaluate the morphology and adhesion of BMSCs on microspheres. After incubation under hypoxic conditions for 3 and 7 days, the cell-microsphere constructs were washed with PBS and fixed with 4% formaldehyde for 30 minutes. Then, the samples were perforated with 0.3% Triton X-100 for 30 minutes and subsequently blocked in 5% bovine serum albumin (BSA) solution at 4°C overnight. Afterwards, the samples were incubated in Phalloidin solution and further stained with DAPI. Finally, the stained cell-microspheres were observed using fluorescence microscopy, and the results are shown in Figure 2. Figure 6D shows the formation of F-actin filaments and cytoskeletal networks within live BMSCs attached to hydrogel microspheres. BMSCs cultured on GM surfaces showed restricted diffusion, indicating impaired cell adhesion. In contrast, BMSCs attached to CSP-GM showed improved spreading morphology, with an ordered cytoskeletal structure and a gradual increase in cellular DAPI, indicating a significant increase in cell number.

[0070] 3. Intracellular Reactive Oxygen Species (ROS) Assay

[0071] To evaluate the level of intracellular reactive oxygen species (ROS), bone marrow stromal cells (BMSCs) and microspheres were placed in the lower and upper layers of the Transwell culture plate, respectively, and incubated in the Anaeropack anaerobic system for 24 hours. Subsequently, BMSCs were incubated with the fluorescent probe DCFH-DA for 0.5 hours in a cell culture incubator at 37 °C and then washed three times with PBS. Finally, the fluorescence intensity of intracellular reactive oxygen species was observed under a fluorescence microscope. The results are shown in Figure 2. Figure 7 As shown in A and B, the fluorescence intensity of the SP-GM and CS-GM groups was significantly reduced compared with the positive control group and the GM group, indicating that the intracellular ROS level was low. In addition, BMSCs treated with CSP-GM exhibited the smallest green fluorescence, showing the strongest ROS scavenging effect, which was further confirmed by quantitative analysis of DCFH-DA fluorescence intensity.

[0072] 4. Mitochondrial Reactive Oxygen Species (ROS) Assay

[0073] MitoSox probe (MedChemExpress, USA) was used to assess mitochondrial reactive oxygen species levels. Bone marrow stromal cells (BMSCs) were incubated in pre-heated MitoTracker Green (100 nM) working staining solution at 37 °C for 30 min. After incubation, the cells were washed several times with PBS and then further incubated with MitoSOX Red (5 μM) working staining solution for 20 min. The ROS fluorescence intensity in mitochondria was then observed under a confocal microscope. The results are shown in Figure 2. Figure 7 As shown in C and D, the mitochondrial ROS level was significantly decreased in BMSCs co-cultured with composite microspheres, among which the CSP-GM group showed the most significant decrease.

[0074] 5. Mitochondrial membrane potential measurement

[0075] The mitochondrial membrane potential (MMP) of bone marrow stromal cells (BMSCs) was evaluated using the JC-1 membrane potential assay kit (MedChemExpress, USA). After 24 h of co-culture with GelMA microspheres in the Transwell co-culture system, the cells were incubated with JC-1 working solution at 37 °C for 20 min, then washed several times with PBS, observed under a fluorescence microscope, and quantitatively analyzed using ImageJ software. The mitochondrial membrane potential was represented by the ratio of JC-1 red / green fluorescence intensity. The results are shown in Figure 7 As shown in E, more JC-1 monomers (green fluorescence) were observed in the control group, while BMSCs co-cultured with composite microspheres showed an increase in JC-1 monomers and a decrease in JC-1 aggregates (red fluorescence) ( Figure 7 E). In addition, quantitative analysis ( Figure 7 F) showed that CSP-GM significantly increased MMP levels compared with the SP-GM and CS-GM groups, indicating that CSP-GM significantly improved the mitochondrial function of hypoxic BMSCs through the synergistic effects of ROS regulation and oxygen supply.

[0076] 6. Scratch test

[0077] Human umbilical vein endothelial cells (HUVECs, 2×10 5 Cells / well) and microspheres were seeded in the lower and upper chambers of a 12-well plate in a Transwell insert, respectively, and cultured in fresh serum-free medium. When the cell confluence reached about 90%, a straight scratch was made on the monolayer using a sterile 100-μl pipette tip. Then, the cells were gently washed several times with PBS to remove floating cells. After 24 hours of co-culture in the Anaeropack anaerobic system, the wound healing was observed under a microscope and quantitatively analyzed using Image J software. The results are shown in Figure 2. Figure 8 As shown, significant cell migration and scratch wound closure were observed in the group treated with composite microspheres, whereas no such results were observed in the control and GM groups within a 24-hour interval ( Figure 8 F). In addition, the 24-hour migration rate of the CSP-GM group was significantly higher than that of the SP-GM and CS-GM groups ( Figure 8 H). These results indicate that the migration ability of ECs is impaired in a hypoxic environment, but the combined effects of oxygen generation and ROS scavenging by CSP-GM significantly promote the accelerated migration of ECs and scratch closure.

[0078] 7. Tube Formation Experiment

[0079] Endothelial cell tube formation assay was used to evaluate the angiogenesis ability of HUVECs in each group. 4Cells / well) were seeded on a 24-well plate pre-coated with Matrigel and then incubated in the Anaeropack anaerobic system to form a vascular network structure. After incubation for 12 hours and 24 hours, the tube formation on the Matrigel surface was observed using an optical microscope, and the results at the 24-hour time point were analyzed. Figure 8 As shown in I and J, only incomplete tubular structures were observed in the control and GM groups, indicating that the angiogenic activity of ECs was limited ( Figure 8 G). Although there was no direct contact between the composite microspheres and the endothelium in the Transwell non-contact co-culture system, the results showed that sustained O2 release significantly promoted the lumen formation process of endothelial cells, demonstrating the development of interconnected vascular-like network structures over time. Quantitative analysis of the newly formed tubular networks showed significant enhancement in several indicators, including the number of connection points and total vessel length in different treatment groups.

[0080] 8. Alkaline phosphatase (ALP) activity assay

[0081] The ALP activity of bone marrow stromal cells (BMSCs) was evaluated by ALP staining and ALP activity quantification kit. After osteogenic induction and 7 days of co-culture in the Anaeropack anaerobic system, the cell-microsphere complex was fixed with 4% formaldehyde solution and washed with PBS, then incubated with ALP staining solution, and the staining results were observed under an optical microscope. For the quantitative analysis of ALP activity, BMSCs and different microspheres were seeded in the lower and upper layers of the Transwell co-culture system, respectively, and the ALP activity was quantified using an ALP assay kit (Beyotime Biotech, China). The results are shown in Fig. 9 As shown in A and B, a significant increase in ALP expression was observed in the CS-GM and CSP-GM groups compared with the GM group. This trend was also supported by the quantitative evaluation of ALP activity, which showed a significant and sustained increase in ALP activity in all experimental groups.

[0082] 9. Alizarin Red (ARS) Staining

[0083] The effect of calcium deposition in different groups was evaluated by ARS staining. After 14 days of co-culture in osteogenic medium, the cell-microsphere complex was washed with PBS and fixed with 4% formaldehyde solution for 30 minutes, then stained with ARS staining kit (Cyage, China), and the calcium nodule deposition was observed under a microscope. Subsequently, the calcium nodule deposition was dissolved in perchloric acid and the absorbance (OD) value at 420 nm was measured. The results are shown in Fig. 9As shown in C and D, the CSP-GM group showed abundant calcium nodules, which exceeded those of the CS-GM and SP-GM groups, while the GM group showed the sparsest calcium nodules ( Fig. 9 C). Quantitative analysis showed that the calcium deposition level in the CSP-GM group was the highest, indicating that its mineralization-promoting effect on BMSCs was superior to that of other groups ( Fig. 9 D).

[0084] 10. Immunofluorescence staining

[0085] Immunofluorescence staining was used to analyze the expression of osteogenic markers in cells cultured on microspheres. Microspheres and cells were co-cultured under hypoxic conditions. After 7 and 14 days of osteogenic induction co-culture, the cell-microsphere complexes were fixed with 4% formaldehyde, permeabilized with 0.1% Triton X-100, and blocked with 5% bovine serum albumin (BSA), and then incubated with primary antibodies specific for Runx2 (7 days) and OCN (14 days) at 4°C overnight, washed with PBS, and incubated with secondary antibodies at room temperature for 2 hours. After washing with PBS, the samples were stained with phalloidin and DAPI. Finally, the stained samples were observed and analyzed using confocal microscopy and ImageJ software. The results are shown in Figure 2. Fig. 9 As shown in EH, the fluorescence intensity of the two proteins in the composite microsphere group increased significantly and gradually, especially in the CSP-GM group. In addition, the expression levels of Runx2 and OCN in the CSP-GM group were approximately 1.7 and 2.9 times higher than those in the GM group, respectively ( Fig. 9 E, 9F), indicating that the bone performance of this group was better than that of other experimental groups.

[0086] 11. qRT-PCR Analysis

[0087] After co-culture with microspheres in the Anaeropack anaerobic system, total RNA of BMSCs was extracted using Trizol reagent at predetermined time intervals. Then, qRT-PCR was used to detect the expression of related genes (Nfe2l2, Hmox1, Sod2, Hif-1α, Vegf, Alp, Runx2, Col 1, Ocn), with glyceraldehyde-3-phosphate dehydrogenase (GAPDH) as an internal reference gene. The relative expression level was measured by 2 -ΔΔCt The results are shown in the figure. Compared with the control group and the GM group, the expression levels of Nfe2l2, Sod2 and Hmox1 in BMSCs treated with composite microspheres were significantly increased, indicating that functionalized microspheres may enhance the resistance of BMSCs to oxidative stress by upregulating the expression of antioxidant genes ( Figure 7G). The results also showed that in addition to multi-level neutralization of excess ROS, CSP-GM also has the potential to enhance the intrinsic antioxidant capacity of BMSCs through the Keap1 / Nrf2 signaling pathway. In addition, the control and GM groups showed higher levels of Hif-1α expression, and the composite microspheres with synergistic oxygen generation and ROS scavenging properties effectively alleviated cellular hypoxia and reduced the expression level of Hif-1α. Although the expression of Hif-1α was reduced in the experimental group treated with nanoparticle-modified microspheres compared with the control and GM groups, a significant increase in Vegf expression was observed, with the CSP-GM group showing the highest expression level ( Figure 8 AD). Under the hypoxic microenvironment, the composite oxygenated hydrogel microspheres showed the potential to promote angiogenesis by regulating the expression of Hif-1α and Vegf, which is essential for vascularization and functional cell protection during bone healing. Finally, in the evaluation of osteogenic potential, after 7 days of culture on the composite microspheres, the expression level of Runx2 in the cells was significantly increased, and the expression of the early osteogenic gene Alp and the late osteogenic marker gene Ocn also increased ( Fig. 9 IK). Notably, the expression of these osteogenic genes was significantly enhanced in the CSP-GM group compared with the SP-GM and CS-GM groups, which was consistent with the results evaluated by ALP and ARS. These convincing results suggest that the synergistic effects of sustained oxygen production and ROS scavenging significantly enhance early and late osteogenic differentiation in a hypoxic microenvironment.

[0088] Example 4

[0089] 1. Establishment of rat femoral condyle defect model

[0090] Male Sprague-Dawley (SD) rats weighing 300-350 g were selected for experimental operation to prepare the femoral condyle bone defect model. Before surgery, the rats were anesthetized by intraperitoneal injection of 2% sodium pentobarbital (2.5 ml / kg). After successful anesthesia, an incision was made on the lateral side of the rat knee joint, and the lateral femoral condyle was exposed by blunt separation of the intermuscular space, protecting the adjacent blood vessels and soft tissues. Then a 3 mm diameter drill was used to drill through the double cortex of the femoral condyle to construct the femoral condyle bone defect. After washing with sterile saline solution, the corresponding sterilized microspheres were filled into the defect, and the surgical incision was carefully sutured in layers. No material was implanted in the control group. After surgery, all rats received intramuscular injections of penicillin every day for 3 consecutive days to prevent infection.

[0091] 2. Radiographic evaluation

[0092] At 2 and 4 weeks after surgery, the rats were euthanized and femoral specimens were collected and fixed with 10% formaldehyde solution. Subsequently, these specimens were scanned by micro-CT (SkyScan1176, Belgium) with specific settings: 18 μm slice thickness, 65 kV, and 500 μA. Then, three-dimensional (3D) reconstruction was performed, and bone morphometric parameters including bone mineral density (BMD), bone tissue volume / total tissue volume (BV / TV), trabecular thickness (Tb.Th), and trabecular space (Tb.Sp) were measured and analyzed. The results are shown in Fig.10 As shown, there was almost no new bone formation in the femoral condyle area (sagittal plane) of the blank control group, and no signs of healing were observed during the healing process. In contrast, the defect area treated with composite microspheres showed more new bone growth and satisfactory bone integration, and this difference increased significantly over time. The CSP-GM group showed significantly better repair effects at both time points, and the defect area was completely filled with new bone at 4 weeks, while in the SP-GM and CS-GM groups, obvious deficiencies were still visible in the central area of ​​the defect area. Micro-CT-3D reconstruction provided a more accurate visual effect of new bone formation across groups. The osteoinductive properties of the SP-GM and CS-GM groups were better than those of the GM group, and the most new bone formation was observed in the CSP-GM group. These results suggest that the combination of oxygen release and ROS scavenging may have a synergistic effect on enhancing bone regeneration. In addition, analysis of BV / TV and BMD confirmed that new bone formation within the defect area increased over time ( Fig.10 DG). At 4 weeks, the BV / TV and BMD in the CSP-GM group were significantly higher than those in all other groups, indicating that a larger volume of mature new bone was formed in the defect area. In addition, cancellous bone microarchitectural parameters were analyzed, including Tb.Sp and Tb.Th. Fig.10 As shown in F and 10G, the GM group had higher Tb.Sp but lower Tb.Th values ​​compared with the SP-GM and CS-GM groups. In addition, the CSP-GM group showed the largest Tb.Th and smallest Tb.Sp values, which were consistent with the morphological results. The radiological results of the GM group showed that its bone regeneration effect was better than that of the control group, which was mainly due to the enhanced osteoconductivity of the biomimetic microstructure of GelMA microspheres over the blank control group.

[0093] 3. Histological Analysis

[0094] Rat femoral specimens were fixed in 4% formaldehyde solution for 48 hours and then decalcified with 10% EDTA solution at room temperature for 30 days. After decalcification, the femoral specimens were embedded in paraffin and cut into 5-micron thick sections along the sagittal axis. The obtained sections were subsequently stained with hematoxylin-eosin (H&E) and Masson's trichrome to analyze the morphological differences in the defect area. At the same time, in order to evaluate the osteogenic capacity, angiogenesis and antioxidant effects in the composite microspheres, immunofluorescence staining of specific markers (Hif-1α, Nrf2, CD31, Runx2 and OCN) was performed. The results are shown in Fig.11 As shown in the figure, H&E staining showed that the control group mainly showed fibrous tissue formation at the defect site at 2 weeks, and only a small amount of scattered and discontinuous new bone tissue at the edge of the defect at 4 weeks. In contrast, the microsphere-treated group gradually showed bone tissue regeneration over time. The CSP-GM group showed dense and orderly distribution of trabeculae within the defect site, indicating that it significantly enhanced osteogenesis and more bone matrix deposition at 4 weeks. Masson staining further showed that there were sparse blue-stained collagen fiber deposition in the original defect site of the control group, while obvious collagen fibers were observed in the microsphere-treated group, indicating the presence of local new bone formation. Masson staining showed that abundant and orderly collagen deposition was observed in the CSP-GM group with a continuous structure, indicating the maturation and remodeling of the regenerated bone. The CS-GM and SP-GM groups showed similar, but not significant bone regeneration effects. Four weeks after implantation, the residual hydrogel microspheres gradually degraded, and because of their ECM-mimicking structure, they provided a supportive framework for the growth of new bone tissue, which was thus wrapped by the newly generated bone tissue. In addition, the synergistic effect of oxygen delivery and ROS scavenging helps to create a microenvironment conducive to regeneration, effectively regulating cell activity and promoting bone regeneration. This finding suggests that the functionalized microspheres can effectively promote the growth of repair cells and enhance the integration of biomaterials with bone tissue. Bone tissue Hif-1α fluorescence staining showed that the composite microspheres significantly reduced the expression level of Hif-1α in vivo compared with the control group ( Fig.10 B). Although some relief of hypoxia in the bone defect was observed in both the SP-GM and CS-GM groups, there was still a significant difference compared with the CSP-GM group. Fig.10 As shown in B, Nrf2 expression was significantly upregulated in the composite microsphere treatment group compared with the control and GM groups. In addition, among the three composite microsphere groups, the CSP-GM group had the most significant increase in Nrf2 expression. The changes in Nrf2 expression were consistent with the levels of ROS and Hif-1α, indicating that oxidized microspheres with ROS scavenging properties can effectively enhance antioxidant activity and alleviate hypoxia. CD31 fluorescence staining showed that blood vessel ingrowth was limited in the control and GM groups, while in the CSP-GM group, a significant increase in CD31 positive expression was observed in both the peripheral and internal areas of the newly formed bone tissue, exceeding that of the other groups ( Fig.12 A, 12D). In addition, immunofluorescence staining was used to detect the osteogenesis of the complex oxygen generation system in the process of bone repair. Fig.12 As shown in Figure 2, the expression levels of osteogenic markers in the groups treated with composite microspheres were significantly higher than those in the control group and the GA group. Quantitative analysis showed that the immunofluorescence signals of Runx2 and OCN in the CSP-GM group were the strongest, followed by the CS-GM and SP-GM groups ( Fig.12 These results suggest that CSP-GM combined with an oxygen generation system with ROS scavenging properties can regulate the microenvironment and effectively promote vascularization and osteogenesis, thereby more effectively accelerating bone tissue repair.

Claims

1. A method for preparing nanoparticle-modified oxygen-producing hydrogel microspheres, characterized in that: The following steps are involved: Calcium peroxide nanoparticles were dissolved in anhydrous ethanol solution, and ammonia water was added after ultrasonic treatment to make the solution evenly suspended. Ethanol and tetraethyl orthosilicate were added dropwise after stirring. After continuous stirring, centrifugation was performed to obtain nano-CaO2@SiO2; nano-CaO2@SiO2 was mixed with dopamine hydrochloride to react to obtain nano-CaO2@SiO2@PDA; nano-CaO2@SiO2@PDA was evenly dispersed in deionized water, activated porous GelMA hydrogel microspheres were added, and nanoparticle-modified oxygen-producing hydrogel microspheres were obtained after stirring.

2. The method for preparing nanoparticle-modified oxygen-producing hydrogel microspheres according to claim 1, characterized in that: The activation method of the porous GelMA hydrogel microspheres comprises: sequentially adding the porous GelMA hydrogel microspheres, 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride and N-hydroxysuccinimide into MES buffer, incubating and centrifuging to obtain activated microspheres; uniformly dispersing nano-CaO2@SiO2@PDA in deionized water, adding the activated microspheres, and stirring to obtain nanoparticle-modified oxygen-producing hydrogel microspheres.

3. The method for preparing nanoparticle-modified oxygen-producing hydrogel microspheres according to claim 2, characterized in that: The incubation condition is 35-40° C. for 10-20 minutes.

4. The method for preparing nanoparticle-modified oxygen-producing hydrogel microspheres according to claim 2, characterized in that: The preparation method of the porous GelMA hydrogel microspheres comprises: using a GelMA solution as an inner dispersed phase and an isopropyl myristate solution as an outer dispersed phase, using a microfluidic device to synchronously polymerize microspheres under ultraviolet irradiation, collecting the obtained GelMA microspheres, purifying them using 75% ethanol and PBS, and then freeze-drying to obtain the porous GelMA hydrogel microspheres.

5. The method for preparing nanoparticle-modified oxygen-producing hydrogel microspheres according to claim 4, characterized in that: The preparation method of the GelMA solution comprises: adding methacrylic anhydride dropwise to a gelatin solution under light-proof conditions, stirring the solution to allow the solution to fully react, adding preheated PBS to terminate the reaction, and continuing stirring; and dialyzing the solution to obtain the GelMA solution.

6. The method for preparing nanoparticle-modified oxygen-producing hydrogel microspheres according to claim 5, characterized in that: The preparation method of the gelatin solution comprises: dissolving gelatin in PBS, and stirring at 50-70° C. for 50-70 minutes to obtain the gelatin solution.

7. The method for preparing nanoparticle-modified oxygen-producing hydrogel microspheres according to claim 1, characterized in that: The preparation method of the calcium peroxide nanoparticles comprises: dissolving anhydrous calcium chloride in double distilled water, then adding ammonia water and polyethylene glycol to the solution under magnetic stirring; gradually adding hydrogen peroxide solution to the mixture through a micropump; after continuous stirring, gradually introducing sodium hydroxide solution and continuously stirring to obtain a suspension; centrifuging the suspension, washing the product and vacuum drying to obtain calcium peroxide nanoparticles.

8. A nanoparticle-modified oxygen-producing hydrogel microsphere, characterized in that: The method is prepared by any one of claims 1 to 7.

9. Use of the nanoparticle-modified oxygen-producing hydrogel microspheres according to claim 8 in the preparation of bone regeneration materials.

10. The use according to claim 9, characterized in that: The bone regeneration material is used for promoting cell survival, stimulating the activation of osteoblasts and vascular endothelial cells and / or alleviating the oxidative stress response in the bone defect microenvironment.